Resistências, poderes e transgressões: discursos de cantoras de rap de São Paulo/SP - Giongo, Flávia Nascimento (2020)
This research aims to address the discourses of gender and diaspora in rap music, composed by black women in the city of São Paulo/SP, between the years 2010 to 2018. For this, it is enrolled in the field of Discourse Analysis, with the guidance given by the philosopher Michel Foucault, with emphasis on the archegenealogical theory of analysis, still related to Cultural Studies in the post-structuralist perspective. On this basis, and starting from the finding that there is a regularity in the themes of the songs of rap women, insofar as issues related to the issues of being a black woman, in their most diverse aspects and intersectionalities, acquire centrality in the musical element of hip hop culture, we set as a problem the question of how the relations of power and knowledge related to discourses about gender and diaspora are objectified and materialized in the music of rap singers from São Paulo/? The general objective, therefore, was to analyze the statements, materialized in the lyrics of the composers/rappers from São Paulo/SP, between the years 2010 to 2018, and, from the songs, understand how these speeches are constructed and replicated and the what they say about themes related to the diaspora and gender. The specific objectives, in turn, were: a) understand how rap, a musical element that is part of hip hop, has historically and discursively consolidated itself as a discursive field, through which various statements of resistance pass; b) to bring the singers experiences closer to the historical moments that defined hip hop and rap, and how they subjectify themselves as subjects of discourse; c) classify the enunciative series, based on the lyrics of the songs, which include speeches related to the diaspora and gender. For this, we seek to understand music as a space for the materialization of speeches, in which the singers occupy spaces of subjects, and through their utterances, present the relations of power and knowledge in force. The chosen procedures and techniques were basically bibliographic analyzes on the subject, semi-structured interviews conducted with the subjects (rap singers - Luana Hansen, Negra San, Sharylaine and Pamelozza). Some of the authors used in the investigation were: Foucault (1974, 1977, 1979, 1984, 1992, 1995, 1996a, 1996b, 1999a, 1999b, 2000 2001, 2008, 2010a, 2010b, 2002), Hall (1997, 2000, 2001, 2003, 2006, 2009), Veiga-Neto (1996, 2000 and 2006), Louro (1997), Fischer (1996, 2001) and Silva (2009 and 2010). With that, the work was structured in a prologue and an introduction, as well as three other sections, in which, after the presentation of the theoretical contribution used in the first section, it was debated about the historical retrospect of hip hop culture in the second, and in the third the views on the enunciative series were operated, and for that purpose, the statements were organized in 03 (three) thematic groups, each with 03 (three) enunciative series, and from them several themes were discussed, among them, black feminism, racism, diaspora, aesthetics, among others. In the end, it can be concluded that the analyzed songs contain powerful speeches of resistance, which bring out various power relations and know that demarcate the lives and bodies of the women interviewed.